Spatial Distribution Pattern of The Fruit Fly, Bactrocera Dorsalis Complex (Diptera: Tephritidae) in Mango Orchard - Soemargono, A.; Muryati, Muryati; Hasyim, Ahsol; Istianto, Mizu (AGRIVITA, Journal of Agricultural Science, 2011)
The spatial distribution of Bactrocera dorsalis complex in the mango orchard that was analyzed using various mathematical indices dispersion and regression models showed an aggregated distribution. Taylorâs power law and Iwaoâs regression model fitted well to all data sets. However, Iwaoâs regression model fitted the data better, yielding higher values of R2 than Taylorâs power law. As the regression of the reciprocal of k of negative binomial (1/k) on x [k = ( x2 â s2/n) / (s2 â x )] was not significant, the calculation of a common k was justified to be 1.30. This implies that the grade of aggregation of the fruit flies population was relatively constant throughout the time despite the variation in sample means. Since the clump size (Î») value was more than 2, the aggregated distribution might be due to the behavior and environmental factors working together.Keywords: Bactrocera dorsalis complex, spatial, distribution, trapping, mango